2012
DOI: 10.1039/c2ra20859h
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted pyrolysis of HDPE using an activated carbon bed

Abstract: Plastics play an enormous role in modern manufacturing, but the extraction and refining of raw materials, followed by the synthesis of plastics themselves, represents an enormous energy investment into a product that is all too often simply "thrown away" into a landfill after a single use. Microwave-assisted pyrolysis is a recycling technique that allows the recovery of chemical value from plastic waste by breaking down polymers into useful smaller hydrocarbons using microwave heat in the absence of oxygen. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(30 citation statements)
references
References 258 publications
0
24
0
Order By: Relevance
“…As previously observed by others in microwave pyrolysis studies [17,18,23,45,46], the interaction of the electromagnetic microwave field with particular types of carbon (e.g., metallic-char) generates "microplasmas" (i.e., electrical discharges resulting from the rapidly oscillating electromagnetic microwave field) which create charge imbalances that are restricted by the physical boundaries of the carbon particles. The temperature of these microplasmas is considerably higher than that of the bulk carbon bed, and consequently waste oil exposed to these microplasmas will be cracked to a greater extent.…”
Section: Product Chemical Composition In the Presence Of Metallic-chamentioning
confidence: 80%
See 1 more Smart Citation
“…As previously observed by others in microwave pyrolysis studies [17,18,23,45,46], the interaction of the electromagnetic microwave field with particular types of carbon (e.g., metallic-char) generates "microplasmas" (i.e., electrical discharges resulting from the rapidly oscillating electromagnetic microwave field) which create charge imbalances that are restricted by the physical boundaries of the carbon particles. The temperature of these microplasmas is considerably higher than that of the bulk carbon bed, and consequently waste oil exposed to these microplasmas will be cracked to a greater extent.…”
Section: Product Chemical Composition In the Presence Of Metallic-chamentioning
confidence: 80%
“…The use of microwave radiation as a heat source is known to offer additional advantages over traditional thermal heat sources [13,14], and the combination of carbon-based material and the novel use of microwave heating in pyrolysis processes is of increasing interest as reflected by considerable recent research reported in the literature [15][16][17][18]. Microwave systems show a distinct advantage in providing a rapid, energy-efficient, and targeted heating process compared to conventional technologies, thus facilitating increased production rates and decreased production costs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Russell et al [76] performed microwave-assisted pyrolysis of HDPE using a reactor bed of catalytic activated carbon. As activated carbon is an excellent microwave absorbent, it served two primary functions: as a catalyst in the pyrolytic cracking of HDPE and also as the enveloping and energy transferring agent necessary for processing microwave-transparent material.…”
Section: Microwave-assisted Pyrolysis Of Polymersmentioning
confidence: 99%
“…A microwave pyrolysis method has been successfully used to pyrolyze a variety of feedstock including waste engine oil (Lam et al, 2010;Lam et al, 2016), wheat straw (Budarin et al, 2009), scrap tires (Appleton et al, 2005;Undri et al, 2013), oil palm biomass waste (Salema & Ani, 2011) and waste plastic (Russell et al, 2012). Valliyappan et al (2008) performed a study on the pyrolysis of glycerol for the production of hydrogen or syngas by using a conventional heating method.…”
Section: Introductionmentioning
confidence: 99%